2011
DOI: 10.1080/02786826.2010.526655
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Emission Characteristics of a Compression Ignition Engine Fueled with Diesel–DMC Blends

Abstract: The effect of fuel composition on the combustion characteristics and particulate emissions of a compression-ignition engine fueled with Euro V diesel fuel blended with dimethyl carbonate (DMC) was investigated experimentally. Blended fuels containing 4.48%, 9.07%, 13.78%, and 18.6% by volume of DMC, corresponding to 3%, 6%, 9%, and 12% by mass of oxygen in the blended fuels, were investigated. By analyzing the measured in-cylinder pressure data and the derived heat release rate, it is observed that the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…The use of DMC resulted in statistically significant increases in particle number emissions compared to CARB ULSD, ranging from 66% to 141%. Our results are in contrast with those seen in previous studies of DMC where particle number emissions showed reductions with higher concentrations of DMC in diesel fuel [21,25,33]. Zhang and Balasubramanian [25] found reductions in particle number emissions of 25.1% and 36.1% for 5% and 10% DMC blends, respectively, based on measurements with a fast mobility particle sizer (FMPS), while Cheung et al [21] also showed reductions in particle number on average of 21% and 37%, for 9.1-18.6% DMC blends, respectively.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The use of DMC resulted in statistically significant increases in particle number emissions compared to CARB ULSD, ranging from 66% to 141%. Our results are in contrast with those seen in previous studies of DMC where particle number emissions showed reductions with higher concentrations of DMC in diesel fuel [21,25,33]. Zhang and Balasubramanian [25] found reductions in particle number emissions of 25.1% and 36.1% for 5% and 10% DMC blends, respectively, based on measurements with a fast mobility particle sizer (FMPS), while Cheung et al [21] also showed reductions in particle number on average of 21% and 37%, for 9.1-18.6% DMC blends, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…This could be a plausible explanation for the higher concentrations of nucleation mode particles with the DMC blends, since DMC possesses a lower boiling point than typical diesel fuel and emits higher levels of nucleation mode particles. Previous studies have shown a shift of the geometric mean diameter of particles towards smaller sizes in comparison to diesel fuel, primarily due to the fuel-borne oxygen [23,33]. Increases in nucleation particles have also been seen in studies of DME [35].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As shown in Fig. 45 Others suggest that oxygen atoms in the ester molecule decompose into two separate reactive oxygen carriers, which then contribute to reductions in soot-precursors. To the contrary, although a number of studies showed consistent reductions in PM with increased biodiesel oxygen content, 18,39 both TPM and TPN increased for the 20% and 50% microalgal biodiesel blends in this study, which have a relatively higher oxygen content.…”
Section: Relationship Between Fuel Oxygen Content and Particle Emissionsmentioning
confidence: 99%
“…Diesel engines are much more efficient than gasoline engines, however, they suffer from NOx and particulate emissions. Many studies have already been reported on the reduction of hydrocarbons, CO, NOx, and particulate emission from diesel engines because of the use of organic carbonates as oxygenate in the fuel [98][99][100].…”
Section: Dimethyl Carbonatementioning
confidence: 99%